2022
DOI: 10.3389/fonc.2022.877635
|View full text |Cite
|
Sign up to set email alerts
|

Cabozantinib sensitizes microsatellite stable colorectal cancer to immune checkpoint blockade by immune modulation in human immune system mouse models

Abstract: Immune checkpoint inhibitors have been found to be effective in metastatic MSI-high colorectal cancers (CRC), however, have no efficacy in microsatellite stable (MSS) cancers, which comprise the majority of mCRC cases. Cabozantinib is a small molecule multi-tyrosine kinase inhibitor that is FDA approved in advanced renal cell, medullary thyroid, and hepatocellular carcinoma. Using Human Immune System (HIS) mice, we tested the ability of cabozantinib to prime MSS-CRC tumors to enhance the potency of immune chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Immune exclusion mechanisms provide potential therapeutic targets that may open the door for MSS CRCs to respond to ICI 67,68 . Biomarkers of immune exclusion may likewise act as predictors of the roughly 30 - 60 % of ICI non-responders in the MSI-H group that are currently immunotherapy candidates 69 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune exclusion mechanisms provide potential therapeutic targets that may open the door for MSS CRCs to respond to ICI 67,68 . Biomarkers of immune exclusion may likewise act as predictors of the roughly 30 - 60 % of ICI non-responders in the MSI-H group that are currently immunotherapy candidates 69 .…”
Section: Resultsmentioning
confidence: 99%
“…Immune exclusion correlates with poor patient outcomes in multiple cancer types and negatively predicts immune checkpoint inhibitor (ICI) response 24,64,65,19,66,28,62 . Immune exclusion mechanisms provide potential therapeutic targets that may open the door for MSS CRCs to respond to ICI 67,68 . Biomarkers of immune exclusion may likewise act as predictors of the roughly 30 -60 % of ICI non-responders in the MSI-H group that are currently immunotherapy candidates 69 .…”
Section: Gene Expression Features Of Cin+ Crcs Predict Immune Exclusionmentioning
confidence: 99%
“…Slightly better results were obtained from the CAMILLA trial, were pMMR mCRC patients who progressed after 2 or more lines of therapy were treated with durvalumab plus cabozantinib. The trial followed preclinical results in which cabozantinib with anti-PD1 showed to slow tumor’s growth and increase expression of the CD4+ T cell ligand HLA-DR on the tumor cells themselves ( 36 ). Despite the different immunotherapeutic agent used, CAMILLA’s efficacy analyses revealed an ORR of almost 30% and a disease control rate of 86.2% (25/29), with a median PFS of 4.4 months and a median OS of 9.1 months ( 37 ).…”
Section: Therapeutic Strategies To Overcome Immunotherapy Resistancementioning
confidence: 99%
“…Moreover, in a humanized mice model, the association of cobimetinib, bevacizumab and pembrolizumab was not able to act on tumor growth. However, an immune modulation in TILs was observed, suggesting that the combination could potentially enhance immune susceptibility in MSS CRC ( 36 ). The use of dual therapy with VEGF inhibitors and immunotherapy has been widely evaluated in many different malignancies, although no thrilling results were obtained in CRCs ( 24 , 45 , 49 , 50 ).…”
Section: Therapeutic Strategies To Overcome Immunotherapy Resistancementioning
confidence: 99%
“…Combination of anti-PD-1 antibody with histone deacetylase inhibitors has also shown successful treatment outcomes in breast cancers [182]. Cabozantinib, a multi-tyrosine kinase inhibitor, sensitized MSS CRC PDXs to anti-PD-1 therapy by increasing the frequency of cytotoxic and IFN-γ + T cells in BRGS humanized mice [181]. This treatment also decreased the expression of T-cell immunoglobulin and mucin-domain containing-3 (TIM-3), which is an inhibitor immune checkpoint and a marker of exhaustion on CD8 + T cells [213,214].…”
Section: Humanized Pdx Mouse Models For Preclinical Testing Of Cancer...mentioning
confidence: 99%